THE CONTRIBUTION OF BUSTHANUL ARIFIN IN LEGISLATING ISLAMIC LAW IN INDONESIA - Iqbal, Muhammad (El -Hekam, 2017)
This paper will elaborate the idea and the effort of Busthanul Arifin in the process of formalizing Islamic Law into an Indonesian national law. The heritage of colonial law has hindered the agenda of Islamization of law in Indonesia mostly by the negative reaction of the ruler. This fact consequence to an uneasy relation between Islam and Political ruler as it is shown along the Indonesian independent era. In this ’war of interest’, most of the time Indonesian Muslim should subjugate their interest. Learned from this trouble relation of Islam and political power in the early of independent era, Bustanul Arifin shoud be marked for his effort to melt the tension and tries to persuade the Indonesian new order ruler in order to obtain and fulfill the aspiration of Muslim people.